Leave of absence due to depression - Carla Danielle Araújo Feitosa; Márcia Astrês Fernandes
Objective: to analyze the occurrence of leave of absence due to depression among workers. Method: census, descriptive-analytical study, with retrospective collection. Population composed of 2,267 workers on leave due to depression with data from the Unified Benefits Information System. The independent variables were: sex, age group, income; county, origin, number of leaves of absence and type of benefit. For data analysis, descriptive statistics were used and the chi-square and Fisher's exact tests were applied. The variables that presented a value of p≤0.20 were submitted to logistic regression. Results: there was a predominance of females, age ≥50 years, from the capital, with income of one to two minimum wages, urban origin and single removal. Single leaves of absence occurred mainly due to a mild depressive episode and the benefit granted to the significant majority was social security sickness benefit. Among those who were on leave of absence more than once, the main cause was recurrent depressive disorder, a current mild episode and, in terms of benefit, social security sickness benefit. There was a statistical association between total time and absence from work. In logistic regression, it was found that the time ≥60 days, was 3.1 times longer in recurrent depressive disorder. Conclusion: there were an expressive quantitative number of absences due to depression, in which it was observed, especially, that the absence time remained long.